The failure of international law to protect Iraqi cultural property from the intentional destruction by ISIS: A priority worthy of international protection - دهش, قائد هادي (Journal of Legal Sciences, 2021)
The destruction and protection of cultural property has been a feature of armed conflicts for thousands of years and it has received increasing international focus over the past two decades. This feature was clearly appeared during the recent armed conflict in Iraq. During the conflict, cultural property was subjected to intentional and organised destruction by members of ISIS. Although there are international legal norms to protect cultural property during armed conflict, however, this destruction has proven the failure of those rules to effectively deter these criminal acts. This Article analyses the framework of international law relevant to the protection of cultural property during of armed conflict in the light of that destruction, and the Article considers whether there are gaps in that framework in relation to the attacks launched by ISIS as a Non-State Armed Group on Iraqi cultural property. By studying recent developments in applicable international law, this Article suggests the need for the international community to announce a third protocol to the 1954 Hague Convention in order to promote international law more effectively and to preserve cultural property for future generations.